(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
This study aims to analyze the legal basis for the authority of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) in resolving land disputes, examine the dispute resolution mechanism through non-litigation channels, and explain the position of ATR/BPN as a facilitator and mediator in realizing legal certainty in land issues. The research method used is normative legal research with a statutory approach and a conceptual approach. Data sources were obtained from primary legal materials in the form of laws and regulations as well as secondary legal materials in the form of books, scientific journals, and expert doctrines relevant to the research object. The results of the study indicate that the authority of ATR/BPN in resolving land disputes has a strong legal basis, namely the 1945 Constitution, Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA), and Regulation of the Minister of ATR/BPN Number 21 of 2020 concerning Handling and Settlement of Land Cases. The non-litigation mechanism is implemented through the stages of complaints, verification, clarification, and mediation. In practice, the ATR/BPN acts as a neutral facilitator and mediator, helping the parties reach an agreement. The implications of this research indicate that the non-litigation mechanism facilitated by the ATR/BPN has the potential to support simpler, more efficient, and more consensus-oriented land dispute resolution in accordance with applicable legal provisions.